Twentieth-Century China as an Object of Thought: An Introduction, Part 1 The Birth of the Century: The Chinese Revolution and the Logic of Politics. (January 2020) - Hui, Wang
This two-part article explores the question of how to constitute China in the twentieth century as an object of thought. This means, first of all, releasing the twentieth century from the position of being a mere object, such that one no longer regards this era as an annotation or appendage to contemporary value systems and ideologies, but instead approaches it as a process in which, passing through the liberation of the object, we may reconstruct a relation of dialogue between ourselves and twentieth-century China. Part 1 proceeds from a temporal analysis of the twentieth century, and Part 2 analyzes this era from a spatial perspective. Part 1 encompasses three sections: first, the long twentieth century, the European fin de siècle, and the century as a trend of the times; second, the conditions of the short century, imperialism, and the rise of the Pacific century; third, the Chinese Revolution and the rise of the short century: unevenness and "the weakest link." Having pursued an analysis of the global conditions of the imperialist epoch, I assert that any discussion of the birth of the "short twentieth century" must begin with an analysis of "the weakest link." In seeking the roots of the revolutionary moment, one must look not at the geopolitical contestations in Eurasia, but instead the revolutionary conditions produced by the new situation in Asia (especially the rise of Japan and Japan's victory over Russia). That is, it was not imperialist wars pure and simple, but instead the "awakening of Asia" called into being by these wars that constituted the multifaceted point of departure for the "short twentieth century." Thus, from the perspective of temporality, the "short twentieth century" did not, as is often believed, begin in 1914, but rather in the period 1905–1911; from the perspective of spatiality, it did not begin at a single point of beginning, but from a whole series of points of beginning; from the perspective of the moment, it did not begin through destructive wars, but instead was born in a series of attempts to break free of the imperialist system and the archaic regime.